Impact of Size and Delay on Neural Activity in the Rat Limbic Corticostriatal System - Roesch, Matthew R.; Bryden, Daniel W. (Frontiers in Neuroscience, 2011)
A number of factors influence an animal’s economic decisions. Two most commonly studied are the magnitude of and delay to reward. To investigate how these factors are represented in the firing rates of single neurons, we devised a behavioral task that independently manipulated the expected delay to and size of reward. Rats perceived the differently delayed and sized rewards as having different values and were more motivated under short-delay and big-reward conditions than under long-delay and small-reward conditions as measured by percent choice, accuracy and reaction time. Since the creation of this task, we have recorded from several different brain areas including, orbitofrontal cortex, striatum, amygdala, substantia nigra pars reticulata, and midbrain dopamine neurons. Here, we review and compare those data with a substantial focus on those areas that have been shown to be critical for performance on classic time discounting procedures and provide a potential mechanism by which they might interact when animals are deciding between differently delayed rewards. We found that most brain areas in the cortico-limbic circuit encode both the magnitude and delay to reward delivery in one form or another, but only a few encode them together at the single neuron level.